Role of Constitutional Courts in the Mechanisms of Implementation of the ECtHR case law - Petrov, Jan, 1981-; Kosař, David, 1979-; Masarykova univerzita. Katedra ústavního práva a politologie (2019)
Tato dizertační práce se zabývá otázkou, jak ústavní soudy států střední a východní Evropy přispěly k vnitrostátní implementaci Evropské úmluvy a judikatury ESLP. Část I představuje rámec pro analýzu mechanismů implementace štrasburského práva, kterou následně aplikuji na Ústavní soud ČR (část II). Na základě případové studie ČR tato dizertace vytváří obecnější teorii vysvětlující role a limity ústavních soudů post-komunistických zemí v implementaci štrasburského práva. Tato teorie je otestována také na analýze maďarského, polského a slovenského ústavního soudu (část III).
This dissertation asks how the Central and Eastern European constitutional courts have contributed to domestic implementation of the European Convention and the ECtHR’s case law. Part I introduces a framework for analysis of ECHR law implementation mechanisms, which is subsequently applied on the Czech Constitutional Court (Part II). Based on the Czech case study, the dissertation presents a general theory explaining the roles and limits of post-communist constitutional courts in ECHR law implementation. This theory is then tested on the Polish, Hungarian and Slovak constitutional courts.
Vedoucí práce: David Kosař
Dizertace (Ph.D.)--Masarykova univerzita, Právnická fakulta, 2019
Keywords: Evropský soud pro lidská práva; Convention for the Protection of Human Rights and Fundamental Freedoms -- (1950 listopad 4.); ústavní soudy; implementace (právo); constitutional courts; Evropa střední a východní; Europe, Central and Eastern; disertace; dissertations